Ramadhan Boarding Schools as Religious Education in Mosque-Based Schools (Analysis of the Implementation of Ramadhan Islamic Boarding Schools in Padang City from an Islamic Education Perspective) - Hakim, Rosniati; Nursa, Ruri Afria (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
Ramadhan Islamic Boarding Schools is an important element in developing the religiosity and character of students in non-formal Islamic education. However, previous studies have focused more on the outcomes of the program rather than the educational space and management actors. This study is aimed at analyzing the implementation of Pesantren Ramadhan in Padang City, with an emphasis on the role of the mosque as the main educational space and the actors involved in managing the program. The research method used in this study was a mixed research method carried out during Ramadhan 1444 H/2023. The research subjects consisted of mosque administrators, parents, and students, who were purposively selected for the study. The study findings revealed that the mosque is considered the most appropriate educational space, as it offers a conducive environment for internalizing religious values and reinforcing students’ affinity for worshiping Allah. Second, the mosque serves as a central coordinating entity with collaborative support from schools, families, and communities, such that integrating these two concepts improves its effectiveness and sustainability. This study has contributed to the importance of synergy in developing mosque-based Islamic education.